Internationalization of higher education institutions under the light of Uppsala theory: case study in business schools - Andrade, Patricia Mara Simões (2021)
Objective: Propose an unprecedented initial categorization structure on the internationalization process of Brazilian HEIs, according to the Uppsala model Methodology: With the qualitative method, semi-structured interviews were conducted with representatives of the HEIs, reviewing and articulating the literature with content analysis on all data obtained.Originality: The study links a classic approach to internationalization with the current reality of higher education institutions. Thus, it is expected that there will be a new conception on how HEIs can optimize their strategies for international insertion.Main results: The internationalization of HEI can be analyzed by three main categorized elements, they are: i) the drivers; ii) enablers and, iii) obstacles to the internationalization of HEIs, each with their own specific characteristics. Theoretical Contributions: The research presents a conceptual categorization for the essential factors of the internationalization of HEI's, this articulation allows advancing in the literature on internationalization and also on the management models of higher education institutions.